2021
DOI: 10.1210/clinem/dgab605
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Microvascular Flow Is Altered in Klinefelter Syndrome and Predicts Circulating Testosterone

Abstract: Context Experimental studies on Klinefelter syndrome (KS) reported increased intratesticular testosterone (T) levels coexisting with reduced circulating levels. Abnormalities in testicular microcirculation have been claimed; however, no studies investigated in vivo testicular blood flow dynamics in humans with KS. Objective To analyze the testicular microcirculation in KS by contrast-enhanced ultrasonography (CEUS) and correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Significant enrichment in Leydig cell within a testicular biopsy sample can 4 Andrologia likely explain the excessive production of testosterone, whereas the markedly increased intratesticular/serum testosterone ratio was believed to result from altered testicular vascularization and dynamic perfusion. These all indicated that impairment of testosterone released into the systemic circulation rather than inhibited testicular steroidogenesis was the cause of hypogonadism in men with KS [21].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Significant enrichment in Leydig cell within a testicular biopsy sample can 4 Andrologia likely explain the excessive production of testosterone, whereas the markedly increased intratesticular/serum testosterone ratio was believed to result from altered testicular vascularization and dynamic perfusion. These all indicated that impairment of testosterone released into the systemic circulation rather than inhibited testicular steroidogenesis was the cause of hypogonadism in men with KS [21].…”
Section: Discussionmentioning
confidence: 90%
“…Our result demonstrated that patients with successful sperm recovery at their 2nd mTESE attempt appeared to have relatively high baseline testosterone and an adequate response to medical treatment. Since better testicular perfusion kinetic, particularly venous blood flow, was associated with relatively higher serum testosterone level [21], we postulated that patients with successful sperm recovery at their 2nd mTESE attempt presented with less disturbed testicular circulation, thus better overall testosterone releasing capability. Additionally, it is plausible that these patients with successful 2nd attempt may have a higher sperm reserve that is sufficient for repeated recovery, which is supported by the fact that improved testicular vascularization correlates with a higher serum testosterone level.…”
Section: Discussionmentioning
confidence: 99%
“…This contradiction has been explained by a disturbed vascularity around the Leydig cells in KS testes since reduced artery diameters were previously found in KS men as well as an increased vessel density of the smallest blood vessels (0–100 µm 2 ) in prepubertal KS tissue [ 33 , 35 , 36 ]. In a recent in vivo study by Carlomagno et al [ 37 ], contrast-enhanced ultrasonography (CEUS) revealed slower testicular perfusion kinetics that was associated with lower total testosterone levels in subjects with KS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine and placental MD predispose to the onset of preeclampsia [46,47] and to early postnatal microvascular rarefaction and development of MD in offspring [48,49]. Finally, testicular MD and penile skin MD are linked to endocrine disturbances and the future development of hypertension and CV diseases [50,51]. Collectively, an integrative approach to understanding MD is needed to implement effective early diagnosis and treatment strategies.…”
Section: Introduction: Microcirculation In Cardiovascular Diseasementioning
confidence: 99%